2018
DOI: 10.1021/acs.biomac.8b00415
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Ring-Opening Copolymerization of Trimethylene Carbonate and Dithiolane Trimethylene Carbonate: Impact of Organocatalysts on Copolymerization Kinetics and Copolymer Microstructures

Abstract: The ring opening copolymerization of trimethylene carbonate (TMC) and dithiolane trimethylene carbonate (DTC) using acidic and basic organocatalysts, i.e., diphenyl phosphate (DPP) and triazabicyclo[4.4.0]dec-5-ene (TBD), was systemically investigated. Interestingly, DPP and TBD gave rise to completely different polymerization kinetics and copolymer sequences. The copolymerization of TMC and DTC using methoxy poly(ethylene glycol) (mPEG-OH) as an initiator and DPP as a catalyst proceeded in a first-order manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 53 publications
2
43
0
Order By: Relevance
“…The gene binding ability of pEt_20 was investigated by agarose gel electrophoresis. DNA extracted from A. baumannii BAA-1709 was mixed with pEt_20 at various polymer to DNA mass ratios (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Briefly, 9.5 µL of the pEt_20/gene complex solution containing 300 ng of gene and corresponding polymer at their respective mass ratios was mixed with 0.5 µL of 5× DNA loading dye.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene binding ability of pEt_20 was investigated by agarose gel electrophoresis. DNA extracted from A. baumannii BAA-1709 was mixed with pEt_20 at various polymer to DNA mass ratios (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Briefly, 9.5 µL of the pEt_20/gene complex solution containing 300 ng of gene and corresponding polymer at their respective mass ratios was mixed with 0.5 µL of 5× DNA loading dye.…”
Section: Methodsmentioning
confidence: 99%
“…Polycarbonates are biodegradable polymers that have been studied for biomedical applications such as drug/gene delivery [19][20][21][22][23][24][25][26][27] and antimicrobial materials [28][29][30] due to their good biocompatibility and ease of incorporating various functional groups. Recently, we reported broad-spectrum antimicrobial guanidinium-functionalized polycarbonates with unique mechanism: membrane translocation followed by precipitation of cytosolic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The copolymerization of CL and DTC using DPP or TBD as catalyst followed a similar procedure with slight modifications: molar ratios of CL/DTC/mPEG-OH/DPP and CL/DTC/mPEG-OH/TBD were adjusted to 9/4/1/10 13 and 9/4/1/0.25, 46 respectively. The applied reaction times are shown in Table 1 , and when TBD was used as catalyst, the reaction was carried out at room temperature (RT) and the termination reagent was replaced by benzoic acid.…”
Section: Experimental Sectionmentioning
confidence: 99%
“… 6 8 These different mechanisms might lead to different polymerization behaviors of monomers, thus yielding copolymers with different structural parameters, e.g ., composition, microstructure ( i.e ., the monomer sequence), and polydispersity, which are important factors that determine the properties of polymers, and thus their applications. 9 13 For instance, it has been demonstrated that an acidic organocatalyst, diphenyl phosphate (DPP), and a basic organocatalyst, TBD, have different ring-opening copolymerization behaviors of cyclic carbonate-based monomers, leading to copolymers with random and blocky microstructures, respectively. 13 In this regard, understanding the role of the catalyst in the kinetics of polymerization becomes important since it offers an important opportunity to satisfy different applications by preparing polymers with different molecular features (monomer sequence, predictable molar masses, narrow molecular weight distribution, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation